STUDI ETNOGRAFI PERILAKU PENGEMIS MASYARAKAT DESA PRAGAAN DAYA KABUPATEN SUMENEP - HARDIYANTINA, RINA; -, SUKARDI (PUBLISIA (Jurnal Ilmu Administrasi Publik), 2016)
Pragaan Daya village in Sumenep Regency is known as the village of beggars, for begging into peoples daily work. Which became the main motive for people to do the work of begging is behavior